2016
DOI: 10.1111/jzo.12371
|View full text |Cite
|
Sign up to set email alerts
|

Health assessment of grey mullet Mugil cephalus based on interrelationship between parasite co‐infections and relative condition factor

Abstract: This study aimed to assess the health status of grey mullet Mugil cephalus by means of relative condition factor under the coexisting parasite groups within seasons. Fish were captured monthly in the Lower Kızılırmak Delta in Samsun, Turkey, from December 2011 to November 2012. A total of five taxonomic groups containing 13 parasite species were constituted: Trichodina (Trichodina puytoraci, T. lepsii), Monogenea (Ligophorus cephali, L. mediterraneus, Gyrodactylus sp., Microcotyle mugilis), Digenea (Ascocotyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…For instance, Lagrue and Poulin (2015) obtained a positive correlation between digenean parasite load and body condition in Gobiomorphus cotidianus McDowall, 1975. Conversely, Özer et al (2016) reported an opposite pattern in Mugil cephalus Linnaeus, 1758 suffering from infections by monogeneans, digeneans and acanthocephalans; whereas in the present study, the correlation between body condition and digenean infections/intensities was insignificant. Inconclusive data on this matter is likely due to direct interactions between hosts and parasites, as well as, external factors affecting both host condition and parasite infection independently.…”
Section: Discussioncontrasting
confidence: 88%
“…For instance, Lagrue and Poulin (2015) obtained a positive correlation between digenean parasite load and body condition in Gobiomorphus cotidianus McDowall, 1975. Conversely, Özer et al (2016) reported an opposite pattern in Mugil cephalus Linnaeus, 1758 suffering from infections by monogeneans, digeneans and acanthocephalans; whereas in the present study, the correlation between body condition and digenean infections/intensities was insignificant. Inconclusive data on this matter is likely due to direct interactions between hosts and parasites, as well as, external factors affecting both host condition and parasite infection independently.…”
Section: Discussioncontrasting
confidence: 88%